The Russian grain market development prospects in the WTO - Чарыкова, Ольга Генсановна; Сальникова, Елена Викторовна (Современная экономика: проблемы и решения, 2015)
Purpose: the identification of the perspective directions of development of the domestic grain market, the evaluation of the factors affecting its potential in the context of the WTO. Discussion: the authors conduct a study of the obstacles to the adaptation of the Russian grain market to the WTO. They analyze risks and threats to Russia’s accession to the WTO on the basis of an assessment of the consequences of Russia’s accession to the WTO. The benefits from Russia’s accession to the WTO are revealed. The scientific works and the research developments in the field of the agrarian policy and the grain market are used as the theoretical and methodological basis of the study. The general scientific and the special methods and approaches such as system, balance, monographic, statistical and economic are applied in the process of the study. Results: the authors prove that the prospects of the grain market should be achieved by building up competitive advantages. The authors consider that the implementation of the defined objectives of the state regulation of the grain market will compensate for the losses and will realize the potential of agro-industrial complex of Russia in the WTO.